Primary cervical malignant melanoma that was successfully treated with pembrolizumab: a case report and literature review - Zhang, Mengpei; Yin, Rutie; Song, Liang; Zhong, Lan; Wang, Ruiyu (Frontiers in Oncology, 2024)
Primary malignant melanoma (MM) arising from the cervix is an exceedingly rare occurrence, and patients diagnosed with this condition often face a dismal clinical prognosis. Herein, we present a case study of a postmenopausal woman presenting with vaginal bleeding and a conspicuous 5-centimeter black mass on the cervix. Based on the staging criteria established by the International Federation of Gynecology and Obstetrics, she was diagnosed with stage IIB primary cervical MM. The patient underwent neoadjuvant therapy prior to a radical hysterectomy and bilateral salpingo-oophorectomy. Subsequently, she completed 18 cycles of Pembrolizumab therapy, achieving clinical complete remission. Notably, at the 31-month follow-up, there were no signs of recurrence. This successful treatment outcome serves as a valuable clinical reference for the management of primary cervical MM.